2009
DOI: 10.1111/j.1365-3156.2009.02423.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a small-scale irrigation scheme on malaria transmission in Ziway area, Central Ethiopia

Abstract: Summaryobjective To assess the impact of a small-scale irrigation scheme in Ziway area, a semi-arid area in the Central Ethiopian Rift Valley, on malaria transmission.method Parasitological, entomological and socio-economic studies were conducted in a village with and a village without irrigation. Blood smear samples were taken from individuals during the dry and wet seasons of 2005 ⁄ 2006. Socio-economic data were collected from household heads and key agricultural and health informants through interviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
106
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(133 citation statements)
references
References 25 publications
15
106
2
Order By: Relevance
“…This finding differs from that of a study in Ethiopia by Kibret and others, in which Table 2 Crude prevalence ratios of demographics, agricultural activities, and crops produced with reported history of malaria among women working in small-scale agricultural on the Makhatini Flats, South Africa, by location (n = 644) * they found a higher prevalence of malaria, in particular during the dry season in a village with an irrigation scheme than in a village that was not irrigated. 7 However, in our study, women on the drylands were more involved in agricultural activities than women in the irrigation scheme and this factor may have contributed to the higher number of malaria cases among women on the drylands. The malaria vectors Anopheles arabiensis and An.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…This finding differs from that of a study in Ethiopia by Kibret and others, in which Table 2 Crude prevalence ratios of demographics, agricultural activities, and crops produced with reported history of malaria among women working in small-scale agricultural on the Makhatini Flats, South Africa, by location (n = 644) * they found a higher prevalence of malaria, in particular during the dry season in a village with an irrigation scheme than in a village that was not irrigated. 7 However, in our study, women on the drylands were more involved in agricultural activities than women in the irrigation scheme and this factor may have contributed to the higher number of malaria cases among women on the drylands. The malaria vectors Anopheles arabiensis and An.…”
Section: Discussionmentioning
confidence: 43%
“…5 Rural agricultural communities in malaria-endemic areas tend to be most at risk for malaria infection, particularly in the presence of intensive irrigation, which provides an ideal breeding ground for the Anopheles mosquito, the vector responsible for malaria transmission. 6,7 Environmental factors such as the distance a person lived from a water source, house typology, and living in a house for more than four years have been associated with an increased risk of developing malaria. [8][9][10] Agricultural activities including land clearing for crop production, which enables surface water pooling suitable for vector breeding, have been associated with an increased incidence of malaria.…”
mentioning
confidence: 99%
“…[30] Another recent study has also reported early biting cycles in Anopheles arabiensis, Anopheles pharoensis and Anopheles coustani in Ziway in central Ethiopia. [31] In this study the man biting rate (MBR) recorded for indoors was significantly higher compared to outdoors man biting rate. In this study indirect calculation of the man-biting from the spray sheet collection was used, the man-biting rate (per night) is obtained by dividing the total number of fed mosquitoes by the total number of individual occupant the houses.…”
Section: Man Biting Rate (Mbr)mentioning
confidence: 89%
“…Agricultural practices have been previously implicated as an occupational risk factor for malaria infection in other settings, including palm oil plantations in Papua New Guinea, irrigated rice paddies in Ethiopia and Cote d'Ivoire, and forest settings in Vietnam. [14][15][16][17] In one study, agricultural irrigation was associated with greater abundance of anopheline vectors in rural Tanzania. 18 In contrast, one study in Peru found that agricultural practices were statistically associated with lower malaria incidence rates.…”
Section: Discussionmentioning
confidence: 99%